On Why ‘Trust’ Constitutes an Appropriate Synonym for ‘Certainty’ in Wittgenstein’s Sense: What Pupils Can Learn from Its Staging - Ariso Salgado, José María (Studies in Philosophy and Education, 2025)
In this paper I outline the most relevant traits of the term ‘trust’ understood as one of the synonyms for ‘certainty’ that Ludwig Wittgenstein used in his posthumous work On Certainty. To this end, I analyze the paragraphs of On Certainty in which reference is made to pupils who are expected to trust what is taught by their teacher: in addition, I note that such a process is largely based on the attitude of rejection and bewilderment that teachers promote towards people who call into doubt those certainties that pupils are expected to assimilate. Subsequently, after emphasizing the importance that Wittgenstein attached to the ineffability of certainties, I explain how such certainty or trust can be staged. Lastly, I clarify why an appropriate contemplation of this staging can be of great help for pupils to achieve at least four goals of educational interest: thus, children can not only strengthen their capacity for wonder, but also experience what things are ineffable, glimpse the limits of rationality, and become more tolerant of people who are partakers of a different world-picture.
Keywords: trust; certainty; doubt; ineffability; wonder; Wittgenstein; Scopus; JCR